The Role of Teachers as Organizers in Madrasah Ibtidaiyah Learning: A Literature Review from an Islamic Perspective - Robby Lafadza Yasin; Iis Arifudin; Ria Yulia Gloria (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
Education from an Islamic perspective has an important role in the formation of people who have faith, knowledge, and noble character. Teachers are the main element in the success of education because teachers are also organizers in managing the learning process and fostering students. Teachers are not only facilitators in the classroom, but also organizers, supervisors, and people in charge of creating a positive climate. This research aims to analyze the role of teachers as an organization seen through an Islamic perspective, especially based on the Qur'an and Hadith. The method used is a literature review by taking a qualitative approach from various sources of scientific literature in the form of books, journal articles, and official educational documents. The findings of this study show that from an Islamic perspective, teachers are positioned as murabbi, mursyid, and muzakki. The role of teachers as organizers is also reflected in how teachers manage classrooms, organize learning activities, instill discipline and moral values, and create an effective educational environment with educational value. The perspective of the Qur'an and Hadith affirms that this organizing task must be based on example, justice, compassion, and moral responsibility. Thus, strengthening the role of teachers as organizers based on Islamic values is an important key in improving the quality of education and forming human resources who are knowledgeable, moral, and pious.